BENDING CHARACTERISTICS OF LAMINATED WOOD COMPOSITES CONSTRUCTED WITH BLACK PINE WOOD AND ARAMID FIBER REINFORCED FABRIC - Karaman, Abdurrahman; Yildirim, Mehmet Nuri; Tor, Onder (Pulp and Paper Research Institute, 2021)
The aim of this study was to determine the 4-point bending strength and modulus of elasticity in bending of Black pine wood laminated materials reinforced with aramid fiber was bonded using epoxy or polyurethane glues separately. The samples were prepared in accordance with the TS 5497 EN 408 (2006). The results of the study determined that the highest value for static bending strength was found in the laminated wood samples (83.94 N.mm-2) that were prepared using inter-layer aramid fiber reinforced polymer (AFRP) and epoxy glue. The highest value of modulus of elasticity in bending was found in the samples prepared with inter-layer epoxy and AFRP (10311.62 N.mm-2). It was observed that the samples parallel to the glue line of the laminated material showed higher performance compared to those perpendicular to the glue line. The data obtained as a result of this study demonstrated that aramid fiber reinforced Black pine wood laminated materials can be used in the building industry as building materials.